SISTEM TATANIAGA BERAS LOKAL MERAUKE DI DISTRIK SEMANGGA - Hironius Letsoin; Niluh Suryaningsih (AGRICOLA, 2012)
This study aims to gain an overview of the implementation of the marketing system of local rice is happening in the district Semangga. The process starts from the farmers, small businessmen, big businessmen and public institutions in the fields of rice, as well as the consumer end of the receiver channel. The study was conducted in April to June 2007 using descriptive methods with interviews techniques directly to the farmer and secondary data collection to the relevant stakeholders. Data were analyzed by tabulation. Primary data was taken on 5 (five) villages in the district Semangga. There are Muram Sari village, Waninggap Kai village, Marga Mulya village, Semangga Jaya village and Bahor village. Secondary data obtained from several related instasi such as the Dinas Tanaman Pangan Kabupaten Merauke and Perum Bulog Sub Divisi Regional Merauke. Local distribution of rice which is managed by the private sector in the District Semangga same as those applied in Indonesia in general the market is through 1st collector (rice mill), 2nd collector (wholesalers/wholesale) and sales/distribution end such as market. The locally rice marketing channel by government in District Semangga is broadly similar. Unless that happens in Marga Mulya village was involving by the Village Unit Cooperatives (KUD) in grain milling